1997
DOI: 10.1071/ea96102
|View full text |Cite
|
Sign up to set email alerts
|

Identifying suitable temperate forage legume species for saline areas

Abstract: Summary. The salt tolerance of 29 lines of annual and perennial forage legume species was evaluated in 4 separate experiments over 0–100 mol NaCl/m3 in the greenhouse with the aim of identifying genetic material that is more salt tolerant than the more traditionally grown forage legume species. Several species or lines showed potential as salt-tolerant germplasm including Trifolium tomentosum, 2 lines of T. squamosum and T. alexandrinum cvv. Mescani and Wardan which were all more salt tolerant than T. subterra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 0 publications
1
25
0
1
Order By: Relevance
“…High salinity increased necrosis and decreased dry biomass of seedlings. These results are in agreement with other studies (Khan and Ungar, 1995;Renault et al, 1998Renault et al, , 2000Rogers et al, 1996Rogers et al, , 1997. Indeed, an excess of sodium salts in plant tissues can lead to enzyme inactivation, inhibition of nucleic acid and protein synthesis, membrane lesions that result in leakage of solutes from the cells and cause injury to tissues (Banuls et al, 1996;Renault et al, 1998Renault et al, , 2000.…”
Section: Dry Matter Production and Survivalsupporting
confidence: 82%
See 1 more Smart Citation
“…High salinity increased necrosis and decreased dry biomass of seedlings. These results are in agreement with other studies (Khan and Ungar, 1995;Renault et al, 1998Renault et al, , 2000Rogers et al, 1996Rogers et al, , 1997. Indeed, an excess of sodium salts in plant tissues can lead to enzyme inactivation, inhibition of nucleic acid and protein synthesis, membrane lesions that result in leakage of solutes from the cells and cause injury to tissues (Banuls et al, 1996;Renault et al, 1998Renault et al, , 2000.…”
Section: Dry Matter Production and Survivalsupporting
confidence: 82%
“…This suggests that there is a high degree of individual resistance within the species and that genetic differences should be considered in the selection of salt tolerant trees. Our results and others (Rogers et al, 1996(Rogers et al, , 1997 suggest that, in order to fully evaluate potential species for saline conditions, it may be worthwhile exploiting the intra-specific variation for dry matter production and survival that exists within species and selecting for increased productivity and survival. Therefore, the use of aggregation indices such as those presented in this study or more refined selection indices appears essential for the selection of seed lots and families, but also for clonal selection within-seed lots or families (Khasa et al, 1995a).…”
Section: Dry Matter Production and Survivalmentioning
confidence: 99%
“…tenufolius L. P. Fourn) is a perennial pasture legume that has naturalized in the flooding Pampa region of Argentina (Kade et al 2003). Previous studies have reported L. tenuis to be salt tolerant (Ayers 1948;Schachtman and Kelman 1991;Rogers et al 1997a) and waterlogging tolerant (Vignolio et al 1999;Mendoza et al 2005;Striker et al 2005) and have suggested this species has potential for use in saline discharge areas (Dear et al 2003). However, the impact of combined salt and waterlogging stress on L. tenuis has not been studied and the mechanisms underlying salt tolerance in L. tenuis have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…While several studies have examined salinity tolerance in the vegetative stage of annual pasture legumes (West and Taylor 1981;Rogers and Noble 1991;Rogers et al 1997Rogers et al , 2008a, few studies have investigated salinity tolerance at germination. West and Taylor (1981) showed reductions in germination of T. subterraneum at concentrations above 70 mM NaCl, while Rogers and Noble (1991) found a 50% reduction in germination of T. michelianum and T. subterraneum in 110 mM NaCl.…”
Section: Introductionmentioning
confidence: 99%